Green synthesis of poly(pyrrole methane)-based adsorbent for efficient removal of chromium(VI) from aqueous solution. (15th April 2021) - Ji, Yajun; Xu, Feiya; Zhang, Panli; Xu, Yuanyi; Zhang, Gaili
Abstract: It has attracted more and more attention to deal with chromium(VI) (Cr(VI)) pollution in wastewater due to its potential harm to human health. In this study, poly(pyrrole methane) (PPm), a potential material for Cr(VI) adsorption, was greenly synthesized for the removal of Cr(VI) from aqueous solution. Further, the Fe3 O4 nanoparticles were loaded on the surface of PPm to enhance the separation property. The adsorption of Cr(VI) was favorable at a lower pH value, and it conformed to Langmuir and pseudo-second-order model. When the solution pH was 2, the dosage of PPm was 0.5 g L −1, the reaction temperature was 45 °C, and the reaction time was 24 h, the maximum adsorption capacity of PPm reached 922.49 mg g −1, which was higher than most of the reported adsorbents (40–560 mg g −1 ). The removal rates reached about 100% even in the presence of competitive ions. The as-prepared adsorbent can be reused for 5 times and the removal rate still exceeded 70%. The adsorption mechanisms of Cr(VI) onto PPm included electrostatic interactions, ion exchange, reduction of Cr(VI) to Cr(III), and immobilization of Cr(III). Although the adsorption capacity of PPm/Fe3 O4 was lower than that of the pure PPm (549.75 mg g −1 ), it can be facilely separated from aqueous solution after adsorption. Notably, this study also provided a facile strategy to prepare adsorbent with active functional groups for efficient removal of Cr(VI) from aqueous solution. Graphical abstract: Image 1 Highlights: A promising poly(pyrrole methane) (PPm) adsorbent was greenly synthesized. PPm showed superior performance for Cr(VI) adsorption. PPm/Fe3 O4 composite was prepared for easy separation and recovery of the adsorbent. The adsorption mechanism of Cr(VI) onto PPm was clarified.